Case reportGeneralized lichen amyloidosis and hyperthyroidism: coincidence or association - Gönül, Müzeyyen; Çakmak, Seray Külcü; Kayaçatin, Serra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
A 76-year-old white man presented with severe pruritic eruption on both of the extremities and lumbar area for 2 years. The dermatological examination showed multiple, 1–2 mm sized, hyperpigmented and hyperkeratotic papules which coalesced to form poorly delineated plaques spread on the lumbosacral area, lateral and extensor surfaces of thighs, arms and forearms. The histopathological examination revealed eosinophilic amorphous material in papillary dermis that was stained positively with crystal violet stain. The patient was diagnosed as generalized lichen amyloidosis (LA) clinically and histopathologically. Routine laboratory tests were within normal limits except thyroid function tests. The thyroid stimulating hormone level was decreased, while the thyroxine level was increased. Ultrasonography showed enlarged and heterogeneous thyroid gland. Thyroid autoantibodies were within normal limits. An association between LA and other diseases such as atopic dermatitis, lichen planus, mycosis fungoides, chronic urticaria, HIV infection, multiple endocrine neoplasia type 2A, and angiolymphoid hyperplasia with eosinophilia have been defined. However, there is no reported LA case associated with hyperthyroidism in the literature. We think that the same etiologic factor might have triggered both diseases, or hyperthyroidism, by causing the itching, might have induced the occurrence or spread of LA.